Associations of Plasma Bioactive Adrenomedullin Levels with Cardiovascular Risk Factors in BRCA1/2 Mutation Carriers - Lammert, Jacqueline; Basrai, Maryam; Struck, Joachim; Hartmann, Oliver; Engel, Christoph; Bischoff, Stephan C.; Berling-Ernst, Anika; Halle, Martin; Kiechle, Marion; Grill, Sabine (Geburtshilfe und Frauenheilkunde, 2022)
Background Cardiovascular disease (CVD) is an important cause of morbidity and mortality in breast cancer survivors. Effective screening modalities to identify CVD risk are lacking in this population. Adrenomedullin (ADM) has been suggested as a biomarker for subclinical cardiac dysfunction in the general population. Levels of ADM have been proven to be responsive to lifestyle changes that lead to improved cardiovascular health. As BRCA1/2 mutation carriers are deemed to be at an increased risk for CVD, the aim of this study was to examine plasma ADM levels in a cohort of BRCA mutation carriers and to assess their association with cardiovascular risk factors.Methods Plasma ADM concentrations were measured in 292 female BRCA1/2 mutation carriers with and without a history of breast cancer. Subjects were classified into high versus low ADM levels based on the median ADM level in the entire cohort (13.8 pg/mL). Logistic regression models were used to estimate the odds ratios (OR) of having elevated ADM levels by several cardiovascular risk factors.Results Of all women (median age: 43 years), 57.5% had a previous diagnosis of breast cancer. The median time between diagnosis and study entry was three years (range: 0 – 32 years). Women presenting with metabolic syndrome had 22-fold increased odds of having elevated ADM levels (p < 0.001). Elevated ADM levels were associated with lower cardiorespiratory fitness (OR = 0.88, p < 0.001) and several parameters of obesity (p < 0.001). ADM levels were higher in women who have ever smoked (OR = 1.72, p = 0.02). ADM levels were not associated with a previous diagnosis of breast cancer (p = 0.28).Conclusions This is the first study in BRCA mutation carriers that has linked circulating ADM levels to traditional cardiovascular risk factors. The long-term clinical implications of these findings are yet to be determined.
Keywords: BRCA1; BRCA2; cardiovascular risk; breast cancer survivors